Bagaimana Meningkatkan Pemahaman Kegiatan Ekonomi melalui Pembelajaran Discovery Learning? (Studi pada Sekolah Dasar Asy Syafi'iyah Surabaya) - Restu Eri Adinata; Nova Septiana; Hervina Renovaka Pradev Devi (Edunusa: Journal of Economics and Business Education, 2022)
This research was conducted with the aim of introducing economic activities to elementary school students through learning with the discovery learning method so as to provide students with an early understanding of economic activities. This research is a classroom action research conducted on students of SD Asy Syafi'iyah Surabaya with two cycle stages. This research was conducted to fourth grade students with a concentration in the field of economics as many as 50 students consisting of two classes. The results of this study indicate that 90% of students who take part in learning have learning outcomes above the minimum limit, and as many as 92% of students are actively involved in participating in the learning process. Based on the final results of the research and discussion, it can be concluded that learning with the discovery learning method can improve the ability of fourth grade students of SD Asy Syafi'iyah Surabaya in understanding economic activities in the field of Social Sciences. It is hoped that further research can bring in more respondents, conduct regular tests and be able to research discovery learning with other methods. So that the next research can discuss more deeply and have a wider scope, then the results obtained will be more comprehensive.